Optimalisasi Supervisi Pengawas Dalam Meningkatkan Mutu Pembelajaran Di Sekolah Dasar - A. Tsabat Izzudin; Sri Susilowardani (UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract: School superintendents have created difficulties in optimizing supervision in improving the quality of learning in schools. The purpose of the study is to map and analyze the optimization of supervisory supervision in improving the quality of learning in elementary schools. Using descriptive qualitative methods, research sources include scientific books, and scientific articles both nationally and internationally related to the optimization of supervising supervision in improving the quality of learning in elementary schools. The results of the study can be concluded that supervisory supervision has not been optimal in improving the quality of learning, it can be seen that the quality of students and teachers is not optimal, the quality of the learning process taking place effectively and efficiently is not optimal, the quality of output from student graduates and student absorption is not optimal. Therefore, the quality of learning can be seen from the quality assurance of inputs, processes, and products produced. Thus, it can be suggested, if you want to improve the quality of learning in elementary schools, then optimize supervision in elementary schools.Keywords: Optimization, Supervisory Supervision, Learning Quality Abstrak: Pengawas sekolah telah menciptakan kesulitan supervisi yang belum optimal dalam meningkatkan mutu pembelajaran di sekolah. Tujuan penelitian untuk memetakan dan menganalisis optimalisasi supervisi pengawas dalam meningkatkan mutu pembelajaran di sekolah dasar. Menggunakan metode kualitatif deskriptif, Sumber penelitian meliputi buku-buku ilmiah, artikel ilmiah baik nasional maupun internasional yang terkait tentang optimalisasi supervivi pengawas dalam meningkatkan mutu pembelajaran di sekolah dasar. Hasil penelitian dapat disimpulkan bahwa supervisi pengawas belum optimal dalam meningkatkan mutu pembelajaran terlihat mutu siswa dan guru belum optimal, mutu proses pembelajaran berlangsung secara efektif dan efisien belum optimal, mutu output dari lulusan siswa dan serapan siswa belum optimal. Oleh karena itu mutu pembelajaran terlihat dari jaminan kualitas input, proses dan produk yang dihasilkan. Dengan demikian dapat disarankan, jika ingin meningkatkan mutu pembelajaran pada sekolah dasar, maka lakukan optimalisasi supervisi di sekolah dasar.Kata Kunci : Optimalisasi, Supervisi Pengawas, Mutu Pembelajaran